Yaothrips shii gen. et sp. n. from western China (Thripidae: Thripinae) - Mirab-Balou, Majid; Wei, Shu-Jun; Lu, Hong; Chen, Xue-Xin (Zootaxa, 2011)
A new genus and micropterous species of Thripinae (Thysanoptera: Thripidae), Yaothrips shii gen. & sp. n., are described and illustrated from Tibet, western China. The relationship of this genus with other genera of Thripinae is discussed, particularly because of a pair of dorso-apical setae on the first antennal segment.